Avoiding perioperative dexamethasone may improve the outcome of patients with rectal cancer. Issue 5 (May 2015) - Yu, H.C.; Luo, Y.X.; Peng, H.; Kang, L.; Huang, M.J.; Wang, J.P.
Abstract Background Perioperative administration of dexamethasone may augment recurrence and mortality after tumor resection possibly by immunosuppression, which, unfortunately, has never been noted. We therefore carried out a retrospective study in rectal cancer to validate the hypothesis. Methods Five hundreds and fifteen patients with stage I to III rectal cancers who underwent a curative resection from June 2007 and June 2011 were enrolled in the current study. Patients who had been given intravenous (IV) dexamethasone (4–10 mg) postoperatively and/or intraoperatively were assigned to dexamethasone group. The outcome of dexamethasone group and non-dexamethasone group were compared. The primary outcome was disease-free survival (DFS) and overall survival (OS). Results dexamethasone group had significant lower three-year DFS (62.3% vs 71.8%, P = 0.026) and OS (74.1% vs 82.9%, P = 0.031) rate in comparison to non-dexamethasone group, the hazard ratios (HRs) of which were 1.59 (95% CI 1.05–2.39, P = 0.028) and 1.77 (95% CI 1.05–3.01, P = 0.034), respectively. Multivariate analysis revealed that administration of systemic dexamethasone were independently associated with DFS [adjusted HR 1.60 (95% CI 1.03–2.49, p = 0.039)], but for OS, dexamethasone didn't remain significant in this model. In the analyses of a subgroup of 428 patients (55/428 in dexamethasone group) without perioperative blood transfusion, dexamethasone had independently impact on both DFS and OS. Conclusion Patients not given dexamethasone had better three-year survival outcomes compared with patients given dexamethasone perioperatively. Our results indicate that rectal cancer patients treated with curative surgery may get survival benefit from avoiding low-dose perioperative dexamethasone.